Structure and use of affirmative and negative constructions in Malaysian English text books / Elesabth Mary Mathalamuthu - Mathalamuthu, Elesabth Mary (2014)
Textbook is a key component in most language programs. In Malaysia, textbooks serve as the basis for much of the language input learners receive and the language practice that takes place in the classroom. In some situations, the textbook may function as a supplement to the teachers’ instruction in the ESL teaching and learning process. For most teachers, textbooks provide the foundation for the content of lessons, the balance of the skills taught, as well as the kind of language practice the students engage in during their classroom activities. To date, many studies focused on the behaviour of English grammatical structures in various national textbooks and questioned the authenticity of the language and grammar presented in these textbooks. This study aims to analyse the structure and use of affirmative and negative constructions in Malaysian English language textbooks and other issues related to it. Thus study is to compare the ways in which affirmative and negative structures are presented in these textbooks and real language use. This was addressed in one of research questions and the design applied was qualitative content corpus analysis. The findings reveal that there are differences in the relative frequency in the use of the affirmative and negative structures. The affirmative structures have higher frequency compared to the negative structures in Malaysian English language textbooks (Forms 3-5). The result of the study also reveals that secondary school learners are not really exposed to many structures and use of different types of negative constructions.